Diseases of dab (Limanda limanda): Analysis and assessment of data on externally visible diseases, macroscopic liver neoplasms and liver histopathology in the North Sea, Baltic Sea and off Iceland. (March 2017) - Lang, Thomas; Feist, Stephen W.; Stentiford, Grant D.; Bignell, John P.; Vethaak, A. Dick; Wosniok, Werner
Abstract: In the framework of the ICON project (Integrated Assessment of Contaminant Impacts on the North Sea), common dab ( Limanda limanda ) from seven offshore sampling areas in the North Sea, Icelandic waters and the western Baltic Sea were examined in 2008 for the presence of externally visible diseases and parasites (EVD), macroscopic liver neoplasms (tumours) (MLN) and histopathological liver lesions (LH). Methodologies applied followed standardised ICES and BEQUALM protocols. The EDV results revealed pronounced spatial variation, with dab from the central and northern North Sea sampling areas showing the highest disease prevalence. MLN were recorded only in North Sea dab from the German Bight, Firth of Forth and Ekofisk at a low prevalence. LH results revealed a dominant prevalence of non-specific, mostly inflammatory, lesions and a low prevalence of early toxicopathic non-neoplastic lesions, tumour pre-stages (foci of cellular alteration) and liver tumours. For the analysis and assessment of spatial variation of EVD, a Fish Disease Index (FDI) was calculated for individual dab, summarising data on the presence/absence of EDV, their severity grades, effects on the host and compensating for effects of length, sex and season. FDI data confirmed that the health status of North Sea dab from the offshore areas Dogger Bank, Ekofisk and Firth of Forth was significantly worse than in dab from the German Bight, Icelandic areas and the western Baltic Sea. An assessment of the disease data following ICES/OSPAR criteria was accomplished by applying established numeric background (BAC) and ecological assessment criteria (EAC) for EDV, MLN and LH. The combined assessment of the three disease categories indicated that health effects classified as unacceptable were rare and mainly affected dab from the North Sea. Based on the findings of the present study, it is recommended to monitor wild fish diseases in the context of assessing the impact of hazardous substances and other stressors on the marine environment. The Fish Disease Index (FDI) is regarded as a strong tool for disease data analysis and assessment, suitable as ecosystem health indicator. Highlights: Marked spatial variation in prevalence of dab diseases occurred in the North Sea, at Iceland and in the Baltic Sea. The health status of dab has improved since the 1980s/1990s. The Fish Disease Index (FDI) proved as a suitable tool for analysis and assessment of fish disease data. ICES/OSPAR assessment criteria for dab diseases were successfully applied.